Management of a case of refractory variant angina with benzhexol hydrochloride (trihexyphenidyl hydrochloride). Issue 4 (October 1985) - Joy, M; Haywood, G A; Webb-Peploe, M M
Abstract : A patient with severe variant angina that was refractory to conventional treatment became symptom free when she was treated with benzhexol (trihexyphenidyl hydrochloride), a cholinergic blocking agent used in the management of Parkinson's disease. There was a brief psychotic reaction when a large dose was taken and some memory impairment on the maintenance dose. Benzhexol should be used with caution but may prove to be an additional therapeutic agent in the management of severe variant angina.